Tantangan Guru Pemula dalam Mengajar Kurikulum Ganda (Nasional dan Keislaman) di Sekolah Dasar Islam - Nurul Hanifah M; Ibnu Muthi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to identify and analyze the challenges faced by novice teachers in implementing a dual curriculum—which includes the national curriculum and Islamic curriculum—in Islamic Elementary Schools (SDI). The dual curriculum in SDI requires integration between mastery of general knowledge and instilling strong Islamic values. However, in practice, novice teachers experience various difficulties, ranging from limited understanding of the two types of curriculum, heavy administrative burdens, to social and cultural pressures of religious schools. This study uses a descriptive qualitative approach based on literature studies, by analyzing relevant academic literature from journals, proceedings, and scientific books in the last ten years. The results of the analysis show that novice teachers experience challenges in pedagogical, structural, psychological, and cultural aspects. They often feel unprepared to develop integrative teaching materials, manage time effectively, and meet institutional and parental expectations. The lack of mentoring, training, and assistance programs also worsen the situation, causing work stress and the risk of burnout. This study concludes that the challenges faced by novice teachers in the context of the dual curriculum are systemic and require a structured and sustainable solution approach, such as strengthening integrated training, integrating curriculum management, and developing a professional development system that supports the pedagogical and spiritual development of novice teachers.